Out-of-Wedlock Pregnancy Among Single Mothers in Khartoum, Sudan: Sociodemographic Characteristics, Causes, and Consequences - Amal Abdelgadir Ali Mohamed; Elshafee Ahmed Apaker Babiker; Sohair Mohmoud Godat; Salma Mohammed Gomaa Doalbet; Aida AF Ahmed; Maha Hamed Mohamed Ali; Abdalkhaliq Ahmed Obadi; Amna Mohammed Ali Mustafa; Amani Awad Elkarim Taha; Amira Elnour Eltayeb Elbashir; Ragaa Gasim Ahmed; Fahad A Alghamdi; et al. (Sudan Journal of Medical Sciences)
Background: Out-of-wedlock childbearing is a global phenomenon that has lifelong consequences on the lives of both mothers and their children. The aim of this study is to identify the sociodemographic characteristics, causes, and consequences of outof- wedlock pregnancy among single mothers in Khartoum, Sudan. Methods: This descriptive, cross-sectional study was conducted at the Mygoma Orphanage Center (MOC) and Shamaa Rehabilitation Center (SRC) using convenience sampling among 200 participants. A validated questionnaire with 25 items was used to collect data. The data were entered into Epi-Data Manager and analyzed using the SPSS. Results: The study found that most of the single mothers in Khartoum who gave birth out of wedlock were young and had just completed their university education. Most of them discovered their pregnancy during the second or third trimester, and nearly half of them did not receive any antenatal care. The majority of the children born to these mothers were preterm and had a low birth weight. Additionally, many mothers reported experiencing social stigma and rejection from their families due to their out-of-wedlock pregnancy. The study also highlighted loneliness, stress, and romantic relations as the main causes of out-of-wedlock pregnancy among single mothers in Khartoum, Sudan. Conclusion: The study provides useful insights into the sociodemographic characteristics, causes, and consequences of out-of-wedlock pregnancy among single mothers in Khartoum, Sudan. Social stigma and lack of support were identified as significant barriers to the reintegration of single mothers and their children into society. Future research should focus on investigating the long-term effects of outof- wedlock pregnancy on mothers and their children.